Sedentary behaviour interventions in young people: a meta-analysis. Issue 11 (1st August 2011) - Biddle, Stuart JH; O'Connell, Sophie; Braithwaite, Rock E
Abstract : Background: There is increasing concern about the time young people spend in sedentary behaviour ('sitting time'), especially with the development of attractive home-based electronic entertainment. This may have deleterious health effects. Purpose: To ascertain, through a meta-analytic review, whether interventions targeted at reducing sedentary behaviours in young people are successful. Method: ERIC, MedLine, PsychInfo, SportDiscus and the Cochrane Library databases were searched up to 2010. Titles and abstracts of identified papers were examined against inclusion criteria. Included papers were coded by three researchers. Results: 17 papers, including 17 independent samples (N=4976), met the inclusion criteria and were analysed. There was a small but significant effect in favour of sedentary behaviour reduction for intervention groups (Hedges' g = − 0.192; SE = 0.056; 95% CI = −0.303 to −0.082; p = 0.001). Moderator analyses produced no significant between-moderator results for any of the intervention or study characteristics, although trends were evident. Conclusion: Behaviour change interventions targeting reductions in sedentary behaviour have been shown to be successful, although effects are small. More needs to be known about how best to optimise intervention effects.